2017
DOI: 10.1111/mec.14097
|View full text |Cite
|
Sign up to set email alerts
|

Chasing ghosts: allopolyploid origin of Oxyria sinensis (Polygonaceae) from its only diploid congener and an unknown ancestor

Abstract: Reconstructing the origin of a polyploid species is particularly challenging when an ancestor has become extinct. Under such circumstances, the extinct donor of a genome found in the polyploid may be treated as a 'ghost' species in that its prior existence is recognized through the presence of its genome in the polyploid. In this study, we aimed to determine the polyploid origin of Oxyria sinensis (2n = 40) for which only one congeneric species is known, that is diploid O. digyna (2n = 14). Genomic in situ hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…allopolyploidisation 29 , 30 ). Unknown lineages underlie the genetic makeup of some polyploid plants 31 and fishes 32 . Such taxa may be more frequent than imagined in vertebrates, especially in amphibians and fishes where these reproductive modes have been well-documented 9 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…allopolyploidisation 29 , 30 ). Unknown lineages underlie the genetic makeup of some polyploid plants 31 and fishes 32 . Such taxa may be more frequent than imagined in vertebrates, especially in amphibians and fishes where these reproductive modes have been well-documented 9 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Their isolated origins and distributions in the sky islands could have evolved in a similar manner to E. baimashanicum with hybrid origin, as discussed above. The polyploid species replaced the sympatric progenitors after the origin because of increased colonization abilities (Otto et al, ; Luo et al, ). Therefore, geographic isolation, hybrid speciation, and polyploidization might have together contributed to the fast species diversification of plants in the sky islands.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, single‐ or low‐copy nuclear markers and chloroplast DNA are used in molecular phylogenetics to detect allopolyploidization events and determine the progenitors of polyploids (Sang, ; Schuettpelz & al., ; Rothfels & al., ). Recent biotic niche studies found that most polyploids inhabited a geographic range between that of the progenitors and had a high degree of niche overlap with their progenitors (Marchant & al., ; Spoelhof & al., ), but significant ecological divergence between allotetraploids and their putative progenitors was detected in other studies (Wu & al., ; Luo & al., ).…”
Section: Introductionmentioning
confidence: 97%